Implications for patient follow-up of changes in inferior vena cava filter removal plan practices. Issue 10 (October 2022) - Siah, T.H.; Habib, Z.; McWilliams, R.G.; Chan, T.Y.
Abstract : AIM: To assess the improvements during patient follow-up after implementing a proactive plan for retrieval of inferior vena cava (IVC) filters. MATERIALS AND METHODS: A retrospective study was undertaken including all patients who had a temporary IVC filter inserted over a 10-year period. Patient demographics, insertion dates, retrieval dates, retrieval rates, and complications were recorded. Patients were categorised into three groups as follows: group A, no intervention where retrieval was not suggested; group B, passive intervention where retrieval was suggested but no appointment made; and group C, proactive intervention where a retrieval date was booked by the radiologist. RESULTS: Five hundred and nine patients had a temporary IVC filter inserted at Royal Liverpool University Hospital over the study period. One per cent of patients in group C were lost to follow-up compared to 41% and 29% in groups A and B respectively ( p <0.001). The number of patients who had an IVC retrieval attempt also increased to 80% in group C compared to 53% and 64% in groups A and B ( p< 0.001). CONCLUSION: Incorporation of a proactive retrieval booking system has significantly reduced the number of patients lost to follow-up to 1%, leading to an increased number of IVC filter retrieval attempts. Highlights: Inferior Vena Cava filter (IVCF) retrieval rates remain poor. Active retrieval plan introduced to reduce lost to follow-up rate. Automatic retrieval appointments generated immediately after IVCF insertion. Plan reduces lost to follow-up rate and increases number of retrieval attempts.